Analisis Minat Belanja Konsumen Dalam Memilih Fashion Di Store Wiratna Modes Dalam Perspektif Ekonomi Syariah - Azizah, Nisa'ul; Afandi, Nihro; Amrullah, A. Afif (Journal of Islamic Economics Studies and Practices, 2023)
In the global era, the business world is facing rapid progress. Business actors must be able to fulfill what consumers need and want so that consumers feel satisfied. Apart from that, you must also have a professional marketing strategy so you can compete with other marketers operating in the same field. Store Wiratna Modes is a Muslim fashion store that pays attention to the compatibility between product quality and the price offered to consumers. The aim of this research is to find out about consumer shopping interest in choosing fashion at the Wiratna Modes Store from a sharia economic perspective. This research is a qualitative description with primary data sources from interviews with store owners and employees as well as several consumers. The results of this research show that consumer buying interest is influenced by internal and external factors. Apart from that, Products, Prices, Promotions, Locations and Services too. And based on analysis from researchers, Store Wiratna Modes has implemented sharia principles in serving its consumers